2023
DOI: 10.3390/plants12061245
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review on Cannabis sativa Ethnobotany, Phytochemistry, Molecular Docking and Biological Activities

Abstract: For more than a century, Cannabis was considered a narcotic and has been banned by lawmakers all over the world. In recent years, interest in this plant has increased due to its therapeutic potential, in addition to a very interesting chemical composition, characterized by the presence of an atypical family of molecules known as phytocannabinoids. With this emerging interest, it is very important to take stock of what research has been conducted so far on the chemistry and biology of Cannabis sativa. The aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 179 publications
0
25
1
Order By: Relevance
“…51 Cannabis has been used to treat epilepsy, 52 cholera, 53 and insomnia, 54 but its cultivation is currently banned in most countries. 55 However, due to its excellent pharmacological efficacy, several studies have shown that cannabis ingredients can cause addiction and mental deterioration. 56 A representative component that exhibits psychotropic activity is tetrahydrocannabinol (THC).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…51 Cannabis has been used to treat epilepsy, 52 cholera, 53 and insomnia, 54 but its cultivation is currently banned in most countries. 55 However, due to its excellent pharmacological efficacy, several studies have shown that cannabis ingredients can cause addiction and mental deterioration. 56 A representative component that exhibits psychotropic activity is tetrahydrocannabinol (THC).…”
Section: Discussionmentioning
confidence: 99%
“…Cannabis is an ancient cultivated fibrous plant native to Southeast and Central Asia and has medicinal and psychoactive properties 51 . Cannabis has been used to treat epilepsy, 52 cholera, 53 and insomnia, 54 but its cultivation is currently banned in most countries 55 . However, due to its excellent pharmacological efficacy, several studies have shown that cannabis ingredients can cause addiction and mental deterioration 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Such conflicting findings may be due to individual differences in cannabinoid receptor distribution or genetic poly-morphisms in humans, but it transpires that one major factor relates to the composition of cannabis preparations. In addition to ∆9-THC, cannabis contains a variety of cannabinoids and other psychoactive compounds, including cannabidiol (CBD) [150]. The latter does not share the psychotropic effects of ∆9-THC and has the opposite neural and behavioral effects [151].…”
Section: Cb1 Receptor Pharmacologymentioning
confidence: 99%
“…Hemp contains more than 500 chemical components, including cannabinoids, flavonoids, terpenoids, alcohols, aldehydes, and alkaloids (Liktor-Busa et al, 2021). In adequate doses, all parts of the cannabis plant have therapeutic effects against several illnesses, such as pain, inflammation, and mental illnesses (Hourfane et al, 2023).…”
Section: Macroscopic Observation Of Organsmentioning
confidence: 99%